The Fibrinogen-like Domain of ANGPTL3 Facilitates Lipolysis in 3T3-L1 Cells by Activating the Intracellular Erk Pathway - Simone Bini; Valeria Pecce; Alessia Di Costanzo; Luca Polito; Ameneh Ghadiri; Ilenia Minicocci; Federica Tambaro; Stella Covino; Marcello Arca; Laura D’Erasmo (Biomolecules, 2022)
Background: ANGPTL3 stimulates lipolysis in adipocytes, but the underlying molecular mechanism is yet unknown. The C-terminal fibrinogen-like domain of ANGPTL3 (ANGPTL3-Fld) activates the AKT pathway in endothelial cells. Hence, we evaluated whether ANGPTL3-Fld stimulates lipolysis in adipocytes through the MAPK kinase pathway. Materials and Methods: 3T3-L1 adipocytes were treated with isoproterenol (ISO), ANGPTL3-Fld, or both. Lipolysis was evaluated through the release of free fatty acids (FFAs) in the culture medium. The activation status of intracellular kinases was evaluated with and without the inhibition of the BRAF–ERK arm of the MAPK pathway. Results: ANGPTL3-Fld alone was not able to activate lipolysis, while the combination of ANGPTL3-Fld and ISO determined a 10-fold enrichment of the FFA concentration in the culture medium with an incremental effect (twofold) when compared with ISO alone. ANGPTL3-Fld alone inhibited hormone-sensitive lipase (HSL), whereas the treatment with ISO induced the activation of HSL. The net balance of ANGPTL3-Fld and ISO cotreatment resulted in HSL activation. The results indicate that ANGPTL3-Fld generated an intracellular activation signal involving the MAPK–ERK pathway, possibly through the PDGFRβ—PLCγ-AMPK axis. Conclusion: ANGPTL3-Fld appears to act as a facilitator of lipolysis in adipocytes, and this effect was driven by a signal mediated by a pathway that is different from the canonical β-adrenergic stimulus.